PERLINDUNGAN HUKUM BAGI NASABAH AS AKIBAT PEMBLOKIRAN REKENING SECARA SEPIHAK OLEH BANK X ATASPERMINTAAN NASABAH LAIN - Mochammad Rizky Arie S.; Sudiman Sidabukke; Daniel Djoko Tarliman (Perpustakaan Universitas Surabaya, 2018)
Bank as a intermediary institution has a strategic positioning foreconomy development in Indonesia. In other side,the existenceof bankinginstitution alsorequires society to participate actively in banking activities. Therelation between banking institution and society isin the banking law regulatory.This research will analyzetheaction ofbank Xthat unilaterally blocks AS’Sbankaccount based on request of another customer which causeddisadvantages forAS.The important thing is the existence oflegal protection for customers who aredisadvantaged due bank actions that do not pay attention to the terms of theagreement that has been made, the technical and operational provisions andprudential principles.Between banking institutions and society are need eachother, so legal protection become important to hold public trust to bankinginstitutions.